Method for loading small-size precious metal on molybdenum carbide carrier
The liquid-phase laser melting and pulsed laser irradiation technology loads small-sized precious metal nanoparticles on the molybdenum carbide carrier, which solves the problems of uneven distribution of precious metal particles and complex processes in the prior art, and realizes the efficient preparation of molybdenum carbide-based composite materials with adjustable size and uniform distribution.
Patent Information
- Application Number
- CN202510015611.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In the existing molybdenum carbide doped/loaded precious metal preparation composite materials, high-temperature sintering method leads to easy aggregation of materials, uneven distribution of precious metal particles, and complex and dangerous processes, making it easy to remain impurities.
Liquid-phase laser melting technology and pulsed laser irradiation technology are used to load small-sized precious metal nanoparticles on the molybdenum carbide carrier, and a high-temperature and high-pressure effect is generated instantly through laser to achieve in-situ loading between precious metal particles and molybdenum carbide carrier, avoiding the use of other chemical reagents.
The preparation of molybdenum carbide-based composite materials with adjustable size and uniform distribution of precious metal particles is realized, which simplifies the process, improves safety and efficiency, and avoids impurity residues.
Smart Images

Figure CN119876862A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a technology for preparing a composite material by doping / loading a noble metal with molybdenum carbide, and in particular to a method for loading a small-sized noble metal on a molybdenum carbide carrier. Background Art
[0002] As a non-precious metal material, molybdenum carbide has attracted widespread attention due to its good biocompatibility, photothermal tumor treatment efficacy, and excellent catalytic activity. Molybdenum carbide can adjust the charge density of the loaded metal and change its catalytic behavior. Doping metal elements into molybdenum carbide can improve its wave absorption performance. In order to meet the various application requirements of molybdenum carbide, molybdenum carbide-based composite materials are often established by technical means such as doping and defect engineering.
[0003] At present, the high-temperature sintering method is generally used to prepare composite materials by doping / loading precious metals with molybdenum carbide. The molybdenum carbide-based composite materials prepared by this method are easy to aggregate, and the loaded metal particles are unevenly distributed. In addition, various chemical reagents are inevitably used in the experimental process, which is easy to leave impurities, and the steps are complicated, and the process is cumbersome and dangerous.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for loading small-sized precious metals on a molybdenum carbide carrier to solve the above-mentioned technical problems existing in the prior art.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] The method for loading small-sized precious metals on a molybdenum carbide carrier of the present invention comprises the steps of:
[0008] Step 1) First, based on the liquid phase laser ablation technology, a single Ag or Au or Pt target is ablated in 20 mL of acetone to obtain a uniformly dispersed colloidal solution of Ag or Au or Pt nanoparticles coated with 1 to 2 layers of carbon layers;
[0009] Step 2) Then, pulse laser irradiation technology was used to make 1 mg MoO 3 The powder was in situ carbonized in 10 mL of acetone or ethanol liquid environment to convert into a colloidal solution containing MoC nanoparticles;
[0010] Step 3) Finally, the obtained colloidal solution containing Ag or Au or Pt nanoparticles is mixed with the colloidal solution of MoC nanoparticles and subjected to ultrasonic treatment, and then irradiated with a laser of 355 nm wavelength for 20 minutes to prepare Ag@MoC or Au@MoC or Pt@MoC series composite materials.
[0011] Compared with the prior art, the method for loading small-sized precious metals on a molybdenum carbide carrier provided by the present invention utilizes the high temperature and high pressure effect generated by laser instantaneously to load metal particles and the molybdenum carbide carrier in situ, without adding other chemical reagents such as stabilizers and surfactants, and is simple to operate, green and efficient. Moreover, the size of the loaded precious metal particles is adjustable and evenly distributed. This method provides a new approach and idea for the preparation and application of precious metal nanoparticles loaded on molybdenum carbide carriers. The precious metals involved are Au, Ag, Pt, etc., and the carbon carriers involve molybdenum carbide, graphene, etc., and the method process is described in detail using Ag@MoC and Au@MoC composite materials as examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0013] Figure 1 This is a flow chart of preparing ultra-small-sized precious metal nanocomposites loaded on a molybdenum carbide carrier based on liquid phase laser technology in an embodiment of the present invention.
[0014] Figure 2 TEM and element distribution diagrams of Ag@MoC (a) and Au@MoC (b) in the embodiments of the present invention.
[0015] Figure 3 (a) and (c) XRD patterns of light absorption of Ag@MoC, and (b) and (d) XRD patterns of light absorption of Au@MoC in the embodiments of the present invention.
[0016] Figure 4 The temperature-time curves of Ag@MoC with different concentrations within 10 min under 808 nm laser irradiation in the embodiment of the present invention (a) and the antibacterial performance evaluation of Ag@MoC on two bacteria (E. coil and S. aureus) at different time intervals (0, 10, 30 min) under photothermal action (b). DETAILED DESCRIPTION
[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, which does not constitute a limitation of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0018] First, the terms that may be used in this article are explained as follows:
[0019] The term “and / or” means that either or both of them can be realized at the same time. For example, X and / or Y means both “X” or “Y” and “X and Y”.
[0020] The terms "include", "comprises", "contains", "has" or other similar semantic descriptions should be interpreted as non-exclusive inclusion.
[0021] The contents not described in detail in the examples of the present invention belong to the prior art known to professionals in the field. If no specific conditions are specified in the examples of the present invention, the conditions are carried out according to the conventional conditions in the field or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used in the examples of the present invention, they are all conventional products that can be purchased commercially.
[0022] The method for loading small-sized precious metals on a molybdenum carbide carrier of the present invention comprises the steps of:
[0023] Step 1) First, based on the liquid phase laser ablation technology, a single Ag or Au or Pt target is ablated in 20 mL of acetone to obtain a uniformly dispersed colloidal solution of Ag or Au or Pt nanoparticles coated with 1 to 2 layers of carbon layers;
[0024] Step 2) Then, pulse laser irradiation technology was used to make 1 mg MoO 3 The powder was in situ carbonized in 10 mL of acetone or ethanol liquid environment to convert into a colloidal solution containing MoC nanoparticles;
[0025] Step 3) Finally, the obtained colloidal solution containing Ag or Au or Pt nanoparticles is mixed with the colloidal solution of MoC nanoparticles and subjected to ultrasonic treatment, and then irradiated with a laser of 355 nm wavelength for 20 minutes to prepare Ag@MoC or Au@MoC or Pt@MoC series composite materials.
[0026] In the step 1), the metal target is dissolved in acetone or ethanol at a laser wavelength of 1064 nm or 532 nm, and the size distribution of the obtained metal nanoparticles is uniform and adjustable.
[0027] In step 2), MO 3 The powder was dispersed in acetone or ethanol by ultrasonication.
[0028] The laser wavelength involved in step 3) is 355 nm and the irradiation time is 20 min.
[0029] During the preparation process, no high temperature environment is required, no inert gas protection is required, and no surfactants or stabilizers need to be added.
[0030] The present invention firstly uses liquid phase laser ablation technology to ablate a single Ag or Au target in acetone to obtain uniformly dispersed Ag or Au nanoparticles coated with 1 to 2 carbon layers. In this process, the size distribution of the metal nanoparticles is uniform and adjustable. Then, the oxide MoO is irradiated by pulsed laser technology. 3 The powder is in-situ carbonized in a high-carbon reducing liquid environment (acetone) to become MoC nanoparticles. Finally, a series of composite materials such as Ag@MoC or Au@MoC can be prepared by laser irradiating the mixed solution of metal nanoparticles and MoC. This method improves the traditional metal-doped molybdenum carbide process. It does not require the addition of any other surfactants, stabilizers and other chemical reagents, avoids the generation of other impurity products, and does not require long-term high-temperature heat treatment, which avoids the agglomeration of metal nanoparticles. The loaded metal particles have adjustable particle size and uniform distribution, and are expected to show different potentials in the fields of catalysis and biology. At the same time, this method is simple to operate, green and efficient, and has strong universality. It not only provides a new way and idea for the preparation and application of nanocomposites with small-sized and highly dispersed precious metals loaded on molybdenum carbide carriers, but also expands the new application of liquid laser irradiation technology.
[0031] In summary, the method for loading small-sized precious metals on a molybdenum carbide carrier of the embodiment of the present invention utilizes liquid phase laser irradiation of a mixed solution of metal nanoparticles and molybdenum carbide to directly obtain a molybdenum carbide-based composite material with uniform size distribution of different metal loads. When irradiated with laser, the molybdenum carbide carrier absorbs light energy and generates local high temperature and high pressure, and the metal nanoparticles coated with 1 to 2 layers of carbon layer on the surface are directly loaded on the molybdenum carbide carrier. On the one hand, the present invention expands the application of liquid phase laser preparation technology in material synthesis, and on the other hand, it also provides a new way and basis for in-depth research on molybdenum carbide-based nanocomposites and their applications. It is a new method for molybdenum carbide-based composite materials loaded with metal nanoparticles.
[0032] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the embodiments of the present invention are described in detail with specific embodiments below.
[0033] Example 1
[0034] The specific experimental process is as follows Figure 1 As shown:
[0035] First, a single Ag target was ablated in 20 mL of acetone for 20 min using a 532 nm laser with an output energy of 90 mJ / pulse to obtain uniformly dispersed Ag nanoparticle colloids coated with 1 to 2 carbon layers. Then, a pulsed laser with a wavelength of 532 nm and an output energy of 200 mJ / pulse was used to ablate 1 mg MoO 3The oxide powder was in-situ carbonized in 10 mL of acetone liquid environment to convert into a colloidal solution containing MoC nanoparticles. Finally, the mixed solution of Ag nanoparticles and MoC after ultrasonic treatment was irradiated by 355 nm wavelength laser for 20 minutes to prepare Ag@MoC composite material.
[0036] Example 2
[0037] The specific experimental process is as follows Figure 1 As shown:
[0038] First, a single Au target was ablated in 20 mL of acetone for 20 min using a 532 nm laser with an output energy of 90 mJ / pulse to obtain a uniformly dispersed Au nanoparticle colloid coated with 1 to 2 carbon layers. Then, a pulsed laser with a wavelength of 532 nm and an output energy of 200 mJ / pulse was used to ablate 1 mg MoO 3 The oxide powder was in-situ carbonized in 10 mL of acetone liquid environment to a colloidal solution containing MoC nanoparticles. Finally, the mixed solution of Au nanoparticles and MoC after ultrasonic treatment was irradiated with a 355 nm wavelength laser for 20 minutes to prepare the Au@MoC composite material.
[0039] Morphology and performance testing
[0040] The following morphology and performance tests were performed on the Ag@MoC composite material prepared in Example 1 of the present invention and the Au@MoC composite material prepared in Example 2 of the present invention:
[0041] (1) In order to characterize the morphology of the products of Example 1 and Example 2 of the present invention, the Ag@MoC composite material prepared in Example 1 of the present invention and the Au@MoC composite material prepared in Example 2 of the present invention were observed by transmission electron microscopy, as shown in FIG. Figure 2 As shown in Figure 2, Ag or Au nanoparticles are uniformly distributed on the MoC support. Such a specific structural material may exhibit special properties in catalysis and biological fields.
[0042] (2) In order to further determine the formation and phase of the products of Example 1 and Example 2 of the present invention, light absorption and XRD tests were performed on the Ag@MoC composite material prepared in Example 1 of the present invention and the Au@MoC composite material prepared in Example 2 of the present invention, respectively. Figure 3 (a) and (c) are the light absorption and XRD patterns of Ag@MoC in the embodiment of the present invention. Figure 3 (b) and (d) are the optical absorption and XRD patterns of Au@MoC. Figure 3It can be seen from (a) and (b) in the figure that compared with the light absorption spectra of MoC, Ag and Au alone, the Ag@MoC nanocomposite prepared in Example 1 of the present invention has an Ag ultraviolet absorption peak, and the Au@MoC nanocomposite prepared in Example 2 of the present invention has an Au ultraviolet absorption peak. Figure 3 It can be seen from the XRD patterns (c) and (d) that the Ag@MoC nanocomposite prepared in Example 1 of the present invention has two phases of MoC and Ag. The Au@MoC nanocomposite prepared in Example 2 of the present invention has two phases of MoC and Au. This further shows that Example 1 of the present invention has indeed successfully loaded small-sized Ag nanoparticles on the MoC carrier, and Example 2 of the present invention has indeed successfully loaded small-sized Au nanoparticles on the MoC carrier. These results are consistent with the above TEM results.
[0043] (3) At present, some work has been done on the application of Ag@MoC in photothermal antibacterial. Figure 4 (a) It can be seen that with the increase of Ag@MoC concentration, its temperature continues to rise under 808nm laser irradiation, and can reach up to 45°C. Ag@MoC has excellent photothermal conversion ability. Heat treatment can cause bacterial cell membrane rupture and thus exert antibacterial effect. Figure 4 (b) It can be seen that compared with the blank group, the survival number of two bacteria (E.coil and S.aureus) was significantly reduced under 808nm near-infrared light irradiation for different time periods on Ag@MoC, indicating that Ag@MoC has excellent photothermal synergistic antibacterial ability. + ) plays an important role in killing bacteria. However, the uncontrolled release of Ag from pure Ag nanoparticles + Ions can cause serious cytotoxicity and waste of resources. Therefore, loading Ag nanoparticles on MoC carriers can reduce the amount of Ag and + The ion release is controllable. Moreover, the ultra-small-sized precious metal nanocomposite material loaded on the molybdenum carbide carrier prepared by this method does not contain other harmful chemical reagents and has great application potential in the biological field.
[0044] In summary, it can be seen that the embodiments of the present invention can not only realize the loading of metal nanoparticles on a molybdenum carbide carrier, but also these metal nanoparticles have the advantages of adjustable size and uniform dispersion. The preparation process is easy to operate and low cost. There is no need to add any surfactants and stabilizers, and no high temperature and inert gas protection are required. It has good application prospects in the fields of biology, catalysis, etc.
[0045] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. The information disclosed in the background technology section of this article is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as an admission or in any form that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for loading small-sized precious metals on a molybdenum carbide carrier, characterized in that: Includes steps: Step 1) First, based on the liquid phase laser ablation technology, a single Ag or Au or Pt target is ablated in 20 mL of acetone to obtain a uniformly dispersed colloidal solution of Ag or Au or Pt nanoparticles coated with 1 to 2 layers of carbon layers; Step 2) Then, using pulsed laser irradiation technology, 1 mg of MoO3 powder is in situ carbonized in a 10 mL acetone or ethanol liquid environment to convert it into a colloidal solution containing MoC nanoparticles; Step 3) Finally, the obtained colloidal solution containing Ag or Au or Pt nanoparticles is mixed with the colloidal solution of MoC nanoparticles and subjected to ultrasonic treatment, and then irradiated with a laser of 355 nm wavelength for 20 minutes to prepare Ag@MoC or Au@MoC or Pt@MoC series composite materials.
2. The method for loading small-sized precious metals on a molybdenum carbide carrier according to claim 1, characterized in that: In the step 1), the metal target is dissolved in acetone or ethanol at a laser wavelength of 1064 nm or 532 nm, and the size distribution of the obtained metal nanoparticles is uniform and adjustable.
3. The method for loading small-sized precious metals on a molybdenum carbide carrier according to claim 1, characterized in that: In the step 2), the MO3 powder is ultrasonically dispersed in acetone or ethanol.
4. The method for loading small-sized precious metals on a molybdenum carbide carrier according to claim 1, characterized in that: The laser wavelength involved in step 3) is 355 nm and the irradiation time is 20 min.
5. The method for loading small-sized precious metals on a molybdenum carbide carrier according to any one of claims 1 to 5, characterized in that: During the preparation process, no high temperature environment is required, no inert gas protection is required, and no surfactants or stabilizers need to be added.
Citation Information
Patent Citations
Method for preparing monodispersed and dimensionally-homogeneous noble metal nanospheres
CN102990081A
Conductive carbon black supported noble metal composite material, and preparation method and application thereof
CN108933264A
Method for in-situ preparation of ultra-small precious metal and non-precious metal alloy on carbon carrier
CN114734051A
Method for preparing high-entropy alloy nanoparticles through laser
CN115283685A
Method for constructing supported catalytic material based on laser ablation technology and application of supported catalytic material
CN117380234A